The complete larval development of the mud shrimp Upogebia vasquezi (Gebiidea: Upogebiidae) reared in the laboratory - de Oliveira, Danielly Brito; Martinelli-Lemos, Jussara Moretto; Abrunhosa, Fernando Araújo (Zootaxa, 2014)
The larval development of Upogebia vasquezi consists of four zoeal stages and a megalopa. In the present study, each larval stage was described and illustrated in detail. The first two stages are re-described in order to provide a detailed comparison with the data available for this species recorded in a previous study. The morphological features of all the stages are compared with those of the larvae of other Upogebia species reported previously in the literature. Broad morphological similarities and distinctions were found among most Upogebia species. The main interspecific variations in the morphology of the zoeal stages are the segmentation pattern of the antennular endopod and number of aesthetascs, the number of setae on the scaphognathite and the presence or absence of a mandibular palp.